Особливостi струмових нестабiльностей фосфiдо-галiєвих свiтлодiодiв, опромiнених нейтронами - Конорева, О.В.; Ластовецький, В.Ф.; Ластовецький, В.Ф.; Опилат, В.Я.; Гришин, Ю. Г.; Петренко, I.В.; Пiнковська, М.Б.; Тартачник, В.П. (Видавничий дім "Академперіодика" НАН України, 2008)
GaP LEDs with atypical current characteristics are studied by optical and electrical methods. The thin structure of an S-shaped NDR region which appears in the current-voltage characteristics at low temperatures (100–77 K) after irradiation has become more expressive and possesses the higher oscillation amplitude. The high destructive influence of fast neutrons on the emitting recombination is caused by two factors: the electrical fields of radiation defects and the capture of charged carriers by their levels.